2017
DOI: 10.1111/vde.12466
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blinded, randomized, controlled, crossover evaluation of a zinc methionine supplement as an adjunctive treatment for canine atopic dermatitis

Abstract: This study supports a potential benefit of adjunctive zinc methionine supplementation in CAD. Dogs receiving glucocorticoids may be more likely to benefit. Further studies are needed to substantiate these initial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…One randomized, double-blinded, placebo-controlled study showed an ameliorative effect of zinc methionine supplementation in dogs with mild to moderate, chronic, non-seasonal AD, receiving either cyclosporine or glucocorticoids [107].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…One randomized, double-blinded, placebo-controlled study showed an ameliorative effect of zinc methionine supplementation in dogs with mild to moderate, chronic, non-seasonal AD, receiving either cyclosporine or glucocorticoids [107].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…In a randomized controlled trial investigating the efficacy of an oral fatty acid, vitamin and zinc supplement in 26 dogs with AD sensu lato, which were already controlled with prednisolone or cyclosporine, the administration of systemic antimicrobials for the treatment of bacterial and yeast infections that occurred during the trial was not associated with a significant improvement of skin lesions (assessed by Canine Atopic Dermatitis Lesion Index) or with a clear-cut reduction of PVAS [ 22 ]. In an open trial, the administration of systemic antibacterials in 14 dogs with AD sensu lato and superficial bacterial pyoderma for 4–6 weeks did not result in the significant improvement of skin lesions that were assessed by a modified regional CADESI-3 (i.e., the older iteration of CADESI that has different sensitivity to change compared to CADESI-4) scoring system [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment of bacterial overgrowth/infection and of Malassezia dermatitis in dogs with AD has been recommended [ 18 , 19 , 20 ] and is widely practiced, there are few studies evaluating its efficacy [ 11 , 21 , 22 , 23 ], and none of them report all currently proposed outcome measures for therapeutic trials on canine AD, including the improvement of skin lesions, the improvement of pruritus, and the owner’s assessment of treatment efficacy [ 24 ]. Thus, the aim of this open, observational, combined prospective, and retrospective study was to evaluate the changes in the severity of skin lesions and pruritus, as well as the investigator’s and owner’s assessment of the efficacy of antimicrobial treatment in dogs with AD and skin infections.…”
Section: Introductionmentioning
confidence: 99%
“…Canine atopic dermatitis is a chronic genetically predisposed, inflammatory, and pruritic skin disorder, that likely accompanies dogs throughout life [120]. McFadden et al reported that dogs affected with the disease improved clinical signs (lower Canine Atopic Dermatitis Lesion Index) by receiving allergen treatment (glucocorticoids or ciclosporin) associated with a zinc-containing supplement (zinc methionine, eicosapentaenoic acid, docosahexaenoic acid, and biotin) when compared to dogs receiving the same medication associated to an identical supplement but without zinc methionine [121]. Moreover, dogs that received glucocorticoids combined with the zinc-containing supplement, presented less pruritus, and a reduction of medication was possible for at least four weeks, comparing with dogs receiving ciclosporin and the zinc-containing supplement, which suggests that glucocorticoids enhance zinc absorption [121].…”
Section: Canine Atopic Dermatitismentioning
confidence: 99%